The ideational meaning of Covid-19 health promotion posters: Multimodal discourse - Khusna, Weny Lailla; Hardjatno, Njaju Jenny Malik Tomi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
Indonesian Government has used online posters to deliver the information regarding Covid-19 which is known as the new variant of virus spreading in the world. Covid-19 posters as multimodality discourse coming with two different semiotic modes that explains ideas and information related to Covid-19. The problem of this study was how the posters deliver and represent the idea of Covid-19 discourse through two semiotic modes. This study aims to describe the ideational and representational meaning of two semiotic modes, verbal and visual. This study used qualitative descriptive method. Verbal data was clauses and visual data was images on the poster of Covid-19. The source of data was the poster downloaded from a website https://promkes.kemkes.go.id/. This study used Systemic Functional Linguistics Theory of Halliday (2004) to analyze ideational meaning of the verbal text and Visual Grammar Theory of Kress and Van Leeuwen (2021) to identify representational meaning of the images on the poster. Based on the analysis, verbal text represents the dominance of material process while the images describe the symbolic process. The dominance of material process means the strong intention that the messages deliver to encourage the readers to carry out the activities. Then, conceptual symbolic process and narrative act process represents meaning and experience of the verbal text.